THE DISPUTE BETWEEN SERBIAN LAWYERS AND LAWYERS FROM THE FORMER AUSTRO-HUNGARI ABOUT PROVING BY WITNESSES ON THE OCCASION OF ENACTMENT THE YUGOSLAV CODE OF CIVIL PROCEDURE - Gavrilović, Biljana (Pravni zapisi, 2018)
Prohibition of proving by witnesses had been existing in Serbian code of civil procedure since 1865. But, when the Kingdom of Serbs, Croats and Slovenes was created, it was asked the question of sustainability of this legal institute. Namely, in other parts of the newly created state there was no ban on using witnesses as evidence in civil proceedings, unlike Serbia. Therefore, extensively discussion was developed about permissibility of proving by witnesses on the occasion of unification of civil procedure. Jurists from Serbia were for prohibition of proving by witnesses, but jurists from other parts of the newly created state (especially - across the Danube and Sava (and Drina) rivers) were against that prohibition. Consequently, subject of this analysis are reasons pro et contra permissibility of proving by wetnesses, that were cited on the occasion of enactment the Yugoslav code of civil procedure.